"A little bit of a guidance and a little bit of group support": a qualitative study of preferences, barriers, and facilitators to participating in community-based exercise opportunities among adults living with chronic pain. Issue 23 (6th November 2021) - Dnes, Natalie; Coley, Bridget; Frisby, Kaitlyn; Keller, Anna; Suyom, Jezreel; Tsui, Cindy; Grant, Gillian; Vader, Kyle; Hunter, Judith
Abstract: Purpose: To understand preferences, barriers, and facilitators to participating in community-based exercise opportunities among adults living with chronic pain. Materials and Methods: An interpretive description methodology based on semi-structured interviews was conducted. Adults (age>18 years) living with chronic pain (pain >3 months in duration) were recruited from a multidisciplinary chronic pain clinic in Toronto, Canada. Thematic analysis was used to conceptualize interview data. Results: Fifteen adults living with chronic pain (11/15 women) were interviewed. Four themes regarding preferences, barriers, and facilitators to participation in community-based exercise are described: (1) accessibility (e.g., cost, location, scheduling, and access to program information from healthcare providers); (2) intrinsic factors (e.g., pain, mental health, and motivation); (3) social factors (e.g., isolation, participation with people with similar capabilities, and safe environment); and (4) program factors (e.g., tailored to adults living with chronic pain, gentle exercise, group-based, and delivered by an instructor knowledgeable about chronic pain). Conclusions: Participation in community-based exercise opportunities among adults living with chronic pain may be influenced by accessibility, intrinsic factors, social factors, and program factors. Results provide a foundation of understanding to develop person-centered community-based exercise opportunities that are tailored to meet the preferences of this population. Implications for Rehabilitation: Although community-based exercise is commonly recommended as part of ongoing self-management of chronic pain, there is limited research exploring perspectives towards community-based exercise opportunities from the perspective of adults living with chronic pain. Adults living with chronic pain reported specific preferences, barriers, and facilitators to participating in community-based exercise opportunities, including accessibility, instrinsic factors, social factors, and program factors. Most adults living with chronic pain reported a preference for community-based exercise opportunities that: (1) are delivered by an instructor who is knowledgeable about chronic pain; (2) involve gentle exercise; (3) are group-based; and (4) include other individuals with similar physical capabilities. Healthcare providers, community-based organizations, and researchers should develop, implement, and evaluate person-centered community-based exercise opportunities for adults living with chronic pain that consider their unique preferences, barriers, and facilitators to participation.